Effects of Sleep, Exercise, and Leadership Support on Resilience in Frontline Healthcare Workers During the COVID-19 Pandemic. Issue 5 (21st May 2022) - Kaye-Kauderer, Halley; Loo, George; Murrough, James W.; Feingold, Jordyn H.; Feder, Adriana; Peccoralo, Lauren; Ripp, Jonathan; Pietrzak, Robert H.
Abstract : This manuscript aims to understand the direct and interacting effects of modifiable personal and systemic factors that contribute to psychological distress among frontline healthcare workers during the COVID-19 pandemic. By doing so, we can better identify targets and interventions to decrease distress and promote resilience in the midst of crisis. Abstract : Objective: To evaluate the direct and interacting effects of personal and systemic factors that contribute to psychological distress among frontline healthcare workers (FHCWs) during the COVID-19 pandemic. Methods: Data were collected using a hospital-wide, cross-sectional survey. A multivariable binary logistic regression and relative importance analysis was conducted to identify factors associated with screening positive for C19-distress. Results: A total of 1005 (39.0%, 95%CI - 37.1–40.9%) out of 2579 FHCWs met the prespecified cutoff values for significant symptoms of C19-distress. Fewer sleep hours and lower perceptions of leadership support explained the majority of variance (19.4% relative variance explained [RVE]) in C19-distress, followed by team camaraderie (6.4% RVE), physical exercise (4.9% RVE), and engagement in hobbies (3.2% RVE). Conclusion: These results underscore the importance of restorative behaviors as potential targets to help decrease distress and promote resilience in FHCWs.